A collective enquiry into critical aspects of teaching the concept of angles - Runesson, Ulla (NOMAD Nordic Studies in Mathematics Education, 2007)
This paper describes an approach to teaching that enhances pupils’ learning in mathematics. The model described – Learning study – involves teachers and researchers cooperating in an iterative process, gathering data about teaching and pupils’ learning, analysing the data, planning and revising their teaching. A particular theoretical framework was used as a guiding principle when designing and analysing learning. The goal was to identify aspects critical for learning the angle concept. It is demonstrated how the teachers were able to identify the critical aspects and change the teaching in a way that promoted pupils’ learning. What these critical aspects may entail and what teachers and researchers can learn from a Learning study is discussed.